ANALISIS KEPADATAN TANAH TIMBUNAN PADA PEMBANGUNAN JALAN DAN JEMBATAN BYPASS MAMMINASATA SEGMEN I DAN II, KAB. MAROS, SULAWESI SELATAN - Ratno Pabaru; Yessy C.S. Pandeiroth; Morris S.S.S. Tumanduk (Sustainable Construction (SUSCON), 2024)
In the field of civil engineering, the density of the ground layer in the field is often a problem. Not a few of the construction projects that do compression use cluster ground to raise the ground elevation. The soil used for the cluster material must be compressed so that it can increase support, reduce falls. Compression is one of the most efficient and practical soil repair techniques used in soil work. The soil density in the field requires evaluation as a guarantee of the quality of the work. This study is intended to find out the level of density and stability of the cluster on road builders and bridges bypass mamminasata segments I and II, Kab. Maros. The methodology of this research is to test the characteristics of the soil, then design a composition of the compaction test mixture (proctor standard) to obtain optimal water content. California Bearing Ratio (cbr) assessment to obtain ground support power value. Sand Cone testing to obtain the land density value of the cluster in the field. The results of the research obtained based on the classification of soil according to AASTHO soil are classified into group A-2-7 with the most dominant material type is sandy soil with a few corals. From the results of the CBR test it was concluded that the density value has met the specification with the measure obtained is 8.82% in Quarry Todopulia and 8.68% in Sambueaja quarry.